The Impact of Smartphone Usage On Adolescent Social Interaction in Borongloe Village - Siokal, Brajakson; Wahyuningsih; Akbar Asfar; Sudarman (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2025)
Excessive smartphone use can negatively impact the social behavior of adolescents, including emotional instability. Objective: This study aims to analyze the relationship between smartphone use and the social interaction of adolescents in Borongloe Village. The method used in this study is quantitative with a cross-sectional study design. The sampling technique used is proportional stratified random sampling with a total sample size of 91 respondents, using a questionnaire as the instrument. The relationship test was conducted using the chi-square statistical test with a significance level of <0.05. Results: The results of the study indicate that active smartphone use is more dominant than passive use, the social behavior of adolescents tends to be poorer rather than better, and there is a significant relationship between smartphone use and the social behavior of adolescents in Borongloe Village, Gowa Regency, with a p-value of 0.00 (p < 0.05). This study concludes that there is a significant relationship between smartphone use and the social interaction of adolescents in Borongloe Village, Gowa Regency. Therefore, it is expected that adolescents will become more aware of the negative impacts of excessive smartphone use and that parents and teachers will supervise the use of smartphones by adolescents